Culture on drugs: narco-cultural studies of high modernity - Boothroyd, Dave (Manchester University Press, 2010)
Reconsidering the place of drugs in our culture and the cultural crises they are perceived to endanger, 'Culture on Drugs' argues that the ideas and concepts by which modernity has attained its measure of self-understanding are themselves, in various ways the products of encounters with drugs and their effects